A qualitative study on the effectiveness of displayed health education materials (HEMs) in an immunization clinic of a tertiary care hospital in West Bengal, India - Maumita De; Saikat Bhattacharya; Soumitra Mondal (Epidemiology and Society Health Review (ESHR), 2023)
Background: Health education materials are intended to percolate certain messages to the general population in order to influence their knowledge and attitude toward health issues. The current study aims to determine the effectiveness of health education materials in terms of visibility, attractiveness, and clarity of message perceived by the study participants. Method: A cross-sectional qualitative study was conducted in the immunization clinic of a tertiary care hospital in West Bengal, India, upon 32 caregivers accompanying the children for immunization. Their explanation of the posters was recorded, transcribed, and translated into English. Results were obtained by analyzing data in both MS Excel and Visual Anthropac. Results: Out of 20 displayed posters, 12 were mostly situated around the vaccination table and had a pictorial presentation with child images. Those posters were first noticed by the participants while waiting. After the pile sorting of 10 attractive posters, four were related to child health, four were about nutrition and breastfeeding, and 2 were included under the personal hygiene group. Only a single poster associated with Vitamin A oil was fully understood by all respondents. A total of 6 posters were fully or partially understood by more than 80% of the respondents, whereas 3 posters related to personal hygiene were wrongly interpreted. Conclusion: The health education materials in the immunization clinic may be planned in clear pictorial presentation with less text, so those could be noticed easily and accompanied with audiovisual aids for understanding correctly.